Nutrient requirements of dairy cattle. - Elizondo-Salazar, Jorge Alberto (Agronomía Mesoamericana, 2006)
Linear regression equations have been obtained to directly calculate nutrient requirements of dairy cattle (TDN, DE, ME, NEL, CP, Ca, P, Vitamin A and Vitamin D) on different physiological stages: maintenance, pregnancy and milk production based on NRC nutrient requirements tables. The R-square was calculated for each equation to establish the degree of adjustment.